Advances in Chemical Constituents, Clinical Applications, Pharmacology, Pharmacokinetics and Toxicology of Erigeron breviscapus - Wu, Ruixia; Liang, Yan; Xu, Min; Fu, Ke; Zhang, Yangliu; Wu, Lei; Wang, Zhang (Frontiers in Pharmacology, 2021)
Dengzhanxixin (DZXX), the dried whole plant of Erigeron breviscapus (Vaniot.) Hand.-Mazz., belonging to Compositae and first published in Materia Medica of South Yunnan by Lan Mao in the Ming Dynasty (1368 AD to 1644 AD), is included in Medicinal Materials and Decoction Pieces of the 2020 edition of the Pharmacopeia of the People’s Republic of China. Its main chemical components are flavonoids that mainly include flavonoid, flavonols, dihydroflavones, flavonol glycosides, flavonoid glycosides, coffee acyl compounds, and other substances, such as volatile oil compounds, coumarins, aromatic acids, pentacyclic terpenoids, phytosterols, and xanthones. Among them, scutellarin and 1,5-dicoffeoylquininic acid are the main active components of DZXX. DZXX has pharmacological effects, such as improving cerebral and cerebrovascular ischemia, increasing blood flow, inhibiting platelet aggregation, promoting antithrombotic formation, improving microcirculation, reducing blood viscosity, protecting optic nerves, exhibiting anti-inflammatory properties, scavenging free radicals, and eliciting antioxidant activities. It is widely used in the treatment of cardiovascular and cerebrovascular ischemic diseases, kidney diseases, liver diseases, diabetic complications, and glaucoma. Pharmacokinetic studies have shown that the active components of DZXX have a low bioavailability and a high elimination rate in vivo. Nevertheless, its utilization can be improved through liposome preparation and combination with other drugs. Acute and subacute toxicity studies have shown that DZXX is a safe medicinal material widely used in clinical settings. However, its target and drug action mechanism are unclear because of the complexity of its composition. In this paper, the clinical application and pharmacological toxicology of DZXX are reviewed to provide a reference for further studying its active components and action mechanism.